A Novel in vivo Anti-amnesic Agent, Specially Designed to Express Both Acetylcholinesterase (AChE) Inhibitory, Serotonergic Subtype 4 Receptor (5-HT4R) Agonist and Serotonergic Subtype 6 Receptor (5-HT6R) Inverse Agonist Activities, With a Potential Interest Against Alzheimer’s Disease - Hatat, Bérénice; Yahiaoui, Samir; Lecoutey, Cédric; Davis, Audrey; Freret, Thomas; Boulouard, Michel; Claeysen, Sylvie; Rochais, Christophe; Dallemagne, Patrick (Frontiers in Aging Neuroscience, 2019)
This work describes the conception, synthesis and in vitro and in vivo biological evaluation of novel Multi-Target Directed Ligands (MTDL) able to both activate 5-HT4 receptors, block 5-HT6 receptors and inhibit acetylcholinesterase activity (AChE), in order to exert a synergistic antiamnesic effect, potentially useful in Alzheimer’s disease (AD). Indeed, both activation of 5-HT4 and blockage of 5-HT6 receptors led to an enhanced acetylcholine release, whose depletion would be implied in AD. The preservation of the latter through the inhibition of AChE would complete this approach and lead to an efficiently restoring of the cholinergic neurotransmission. Furthermore, 5-HT4 receptor agonists, also, appear able to promote the non-amyloidogenic cleavage of the amyloid precursor protein and to favor the production of the neurotrophic protein sAPP. This study succeeded in yielding such pleiotropic compounds whose one of them further displayed in vivo an anti-amnesiant effect in a model of scopolamine-induced deficit of working memory from the dose of 0.3 mg/kg.